Pengaturan Suhu Brooding pada Performa Ayam Broiler Pelanggan PT New Hope Indonesia - Fajar Hidayat; Sumiati Sumiati; Rudi Afnan; Roni Fadilah (Institut Pertanian Bogor, 2023)
Genetic improvement through intensive selection in broilers for economically important traits such as body weight, growth rate, feed efficiency, and carcass quality plays a role in increasing the productivity and efficiency of the broiler industry. Good maintenance management is needed by paying attention to the quantity and quality of feed as well as comfortable and controlled environmental conditions. The environmental factor that is often the focus of attention is the temperature of milieu. During the brooding period aged 0‒21 days, the Day Old Chick cannot regulate its body temperature perfectly and still influenced by ambient temperature. Therefore, it is necessary to study the effect of brooding temperature on the performance of broiler at PT New Hope Indonesia's customers, to find the problems in regulating brooding temperatures along with solutions, evaluations, and improvement plans. Observations were made for 21 days in a semi-closed house with a population of 22,000 Cobb strain broiler. The research method used is data recording observation. The primary data were average brooding temperature for 21 days, depletion rate, feed consumption, body weight, feed conversion ratio (FCR), and production index. There was a deviation in body weight and FCR at the age of 11‒14 days due to the restriction of the heater until the age of 14 days and the wind speed at night which was more than 0.3 ms-1. With the corrective action of wind speed regulation, an effective temperature close to the thermoneutral zone and optimal production performance was obtained until the end of the brooding period. Keywords: body weight, broiler, brooding, feed conversion ratio, temperature